2018
DOI: 10.1017/jsl.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

Namba Forcing, Weak Approximation, and Guessing

Abstract: We prove a variation of Easton's lemma for strongly proper forcings, and use it to prove that, unlike the stronger principle IGMP, GMP together with 2 ω ≤ ω 2 is consistent with the existence of an ω 1 -distributive nowhere c.c.c. forcing poset of size ω 1 . We introduce the idea of a weakly guessing model, and prove that many of the strong consequences of the principle GMP follow from the existence of stationarily many weakly guessing models. Using Namba forcing, we construct a model in which there are statio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…By Corollary 1.5 together with Viale's result, ISP does indeed imply SCH. 1 Corollary 1.6. ISP implies SCH.…”
Section: Guessing and Coveringmentioning
confidence: 99%
See 1 more Smart Citation
“…By Corollary 1.5 together with Viale's result, ISP does indeed imply SCH. 1 Corollary 1.6. ISP implies SCH.…”
Section: Guessing and Coveringmentioning
confidence: 99%
“…Viale ([6, Remark 4.3]) asked whether it is consistent to have a guessing model which is not internally unbounded. In [1,Section 4] we showed that PFA implies the existence of stationarily many elementary substructures N of H(ω 2 ) of size ω 1 such that N is guessing but sup(N ∩ ω 2 ) = ω. Such models do not have countable covering, but they are internally unbounded according to Definition 1.3.…”
Section: For a Set Or Classmentioning
confidence: 99%